تحديد بعض معايير التوجيه البدنية و الفسيولوجية لدى مهاجمين كرة القدم تحت 17 سنة - قادة, بومدين; ضيف, هارون; بن قوة, علي; سداوي, شاشو (جامعة الوادي - University of Eloued, 2023)
يهدف البحث إلى تحديد بعض معايير التوجيه العلمية لدى مهاجمين كرة القدم تحت 17 سنة ، حيث قام الباحثون بدراسة أولية لتثمين المشكلة و التي نتج عنها الغياب الشبه تام لاستخدام الأسس العلمية في توجيه اللاعبين نحو منصب الهجوم، وفي خطوة التي خصت الدراسة الأساسية للبحث قام الباحثون بتصميم بطارية اختبارات لعملية التوجيه تحتوي أهم صفات المهاجم لكرة القدم الحديثة، وقد تم تطبيقها على عينة قوامها 60 لاعب مهاجم من عشرة فرق ينتمون إلى الرابطتين الجهويتين وهران و سعيدة وبعد المعالجة الإحصائية تم تحديد مستويات معيارية للقدرات البدنية-الفسيولوجية أسفرت عن مستوى متوسط إلى ضعيف في أغلب النتائج الخاصّة بالمهاجمين، حيث استنتج الباحثون أنّ عملية التوجيه المستخدمة كانت ذاتية وعشوائية دون مراعاة متطلبات المنصب وذلك راجع إلى عملية التكوين والمتابعة التي تحتاج إلى إعادة نظر و دراسة معمقة لإيجاد الصيغ الحقيقة لتطوير مستوى لاعب كرة القدم الجزائرية. Abstract: The research aims to identify some scientific guidance standards for football strikers under 17 years old, where the researchers made a preliminary study to evaluate the problem, which resulted in the almost complete absence of using scientific foundations in directing players towards the attacking position, and in a step that singled out the basic study for the research, the researchers designed A battery of tests for the guidance process containing the most important characteristics of the striker for modern football. It was applied to a sample of 60 attacking players from ten teams belonging to the two regional leagues, Oran and Saida. After statistical treatment, standard levels of physicalphysiological abilities were determined, which resulted in a medium to weak level in most The results of the attackers, where the researchers concluded that the guidance process used was subjective and random without taking into account the requirements of the position, and this is due to the formation and follow-up process that needs to be reconsidered and in-depth study to find the true formulas for developing the level of the Algerian football player
مقال
Keywords: معايري التوجيه– املهامجني - القدرات البدنية- القدرات الفسيولوجية